Field Journal of Henry A. Pilsbry Pertaining to New Mexico and Trans-Pecos Texas - Artie L. Metcalf (Hello World!, 1970)
On file and the Department of Mollusks, Academy of Natural Sciences of Philadelphia (ANSP), are a number a field journals kept by Henry A. Pillsbry during several expeditions to the south western United States and Mexico. The notes are in ink and pencil, faded in some places, and the notebooks are rather poor quality paper. Herein, parts of these journals pertaining to New Mexico and Trans-Picos Texas have been extracted. Four expeditions are involved: 1906, 1910, 1922, and 1935. I was unable to find any notes pertaining to another expedition, which Pillsbry made it to the Black Range of New Mexico in 1915.